Sistema informático móvil de canciones para el reforzamiento del aprendizaje en el idioma Kukama, Asociación Cultural Yrapakatun, Santo Tomas, año 2021 - Alca Arequi, Ciro (2024)
This research has as a general problem: To what extent does the development of a mobile application of songs for Kukama children reinforce the learning of their native language? The general objective being: Develop and implement a mobile computer system of songs for Kukama children to reinforce the learning of their native language”, is of an applied technological type with a descriptive level and the research design is pre-experimental and according to the number of measurements it is transversal, the study population is children whose parents belong to the Yrapakatun cultural association, members of the Kukama community, who live in the town of Santo Tomás, according to this, the sample is 18 children, the data collection procedure was the survey technique with its instrument the questionnaire (Annex 2) and the documentary analysis technique with its instrument the sheet (Annex 3), information processing will be done with Microsoft Excel software. In order to be able to contrast the hypothesis formulated for this research work, which is the following: "The Kukama mobile computer system of children's songs reinforces the learning of their native language." The results obtained show that Satisfaction is 66.67%, which is Good, just like the learning indicator is 86.11%, which fulfills the hypothesis of this research project.